The Endangered Wayu (Hayu) Ethnic Group of Nepal: Examining Policy Gaps in Cultural Preservation (Voice of History, 2025)
The Wayu (Hayu), an indigenous ethnic group in Nepal, face significant socio-political and cultural marginalization. Over time, their cultural heritage has been increasingly threatened due to systemic exclusion and ineffective policy implementation. This study examines Nepal’s public policy framework, including the Constitution of Nepal (2015), the National Foundation for Development of Indigenous Nationalities (NFDIN) Act (2002), the Local Government Operation Act (2017), the National Education Act and Policy (2019), and the Social Security Act (2018), to evaluate their effectiveness in addressing the challenges faced by the Wayu community. Utilizing a qualitative research approach grounded in a transformative paradigm, this study highlights the policy gaps and barriers to the effective implementation of constitutional rights, social justice provisions, and cultural preservation efforts. Despite legal frameworks ensuring equality and inclusion, systemic biases, lack of targeted programs, and poor inter-agency coordination have hindered meaningful progress. The study finds that government policies often adopt a blanket approach that fails to address the specific socio-economic and cultural contexts of smaller communities like the Wayu. Additionally, local government priorities remain skewed toward physical infrastructure, further side-lining marginalised ethnic groups. Education emerges as a crucial factor in cultural preservation and socio-economic empowerment; however, inadequate support for mother-tongue education and limited higher education opportunities exacerbate the cycle of marginalisation. This study underscores the need for reparation policy enforcement with a robust mechanism that are context-specific, inclusive, and actively responsive to the needs of endangered ethnic groups like the Wayu. By addressing these shortcomings, Nepal can ensure the cultural resilience and social justice of its indigenous communities.